Pembuatan Edible Film dari Tepung Jagung (Zea Mays L.)dan Kitosan - Sri Wahyu Murni (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Food packaging is important that affect it’s quality, one of the safe packaging method is to use edible film. Edible film is a thin layer that can be consumed, formed to coat the food that serves to maintain the food quality, as mass transfer barrier (eg, moisture, oxygen, light, lipids, and solute). Edible film also can be used a carrier substance additives to improve the food quality. This research aims to determine the appropriate formulation of material to produce edible film with optimal characteristics. In this casethe main materials used are corn starch and chitosan with the addition sorbitol and glycerol as plasticizer. Edible films made from cornstarch dissolved in distilled water and then heated till 85oC and chitosan dissolved with a solution of 1% acetic acid. Both mixtures were mixed and then plasticizer sorbitol and glycerol were added. After it is molded, and dried at 60°C in 7 hours; it is released from the mold, edible film is ready to use. The results shows that the optimum formulation of edible corn starch and chitosan films are edible film that formed from 7 grams cornstarch, 3 grams of chitosan, 1 ml of sorbitol and 1ml of glycerol, with physical characteristic is 21 , 45 % film solubility; 15,5597 MPa film tensile strength, and water vapor permeability is about 3,089 × 10^-8 g/m.s.kPa